The craft of the cut : the final cut Pro X editor's handbook - Chirtou, Marios (Wiley, 2012)
The art of professional video editingAlthough technology is rapidly evolving, it is still complicated to edit video. This unique book not only teaches you the art of professional editing, it also gives you authentic professional experience. You'll be guided through a typical industry production workflow; you'll have access to raw footage, including alternate takes of each scene from a professional short film; and you'll make your own decisions. By the book's end, you'll have completed your own version of a film. It's the perfect primer for aspiring editors who want to ascend to industry-level.